Economia do desejo e desejo de economia : retroalimentação e troca em coletivos da rede Fora do Eixo no interior de São Paulo - Mazzer, Fernando Lopes (2016)
This research discusses data that was collected at a ethnography in cultural collectives of the Fora do Eixo network situated in cities of the heartland of São Paulo. These collectives are called Fuligem (city of Ribeirão Preto), CECAC (Serrana) and Usiarte (Sertãozinho). The main objective of the research is to describe and to point reflections about the economic dimensions that are brought about by the relations of these collectives between themselves and with agentes who does not belong to the Fora do Eixo network. These agents are know as partners and contributors. For the description of these practices considered as economics, is essential the analysis of a native concept know as collaborative economy. This concept is elaborated and operated by these collectives with different intensities, shades and reaches. On the one hand, I describe how the codes that refer to the collaborative economy are operated and stimulated by the exchanges between the collectives, and on the other hand, I expose how the are theorized in the network instance. I seek to do this with the data collected in reunions, meetings and congresses of collectives that are part of Fora do Eixo network. In this way, the research chooses to ethnographically describe the collectives working as resonance centers of related codes of collaborative economy. These codes are propagated and operated by the collectives throught the so-called tolls and simulacra. Based on the analysis of a simulacra called Fora do Eixo Bank and the tolls called collective house, the collective register and a own currency of Fora do Eixo called card, the research seeks to investigate how the collaborative economy is propagated and operated by the collectives.